2014
DOI: 10.1016/j.ejvs.2014.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Reinforced Aneurysmorrhaphy for True Aneurysmal Haemodialysis Vascular Access

Abstract: Reinforced aneurysmorrhaphy with an external mesh prosthesis is an effective method for treating true aneurysmal haemodialysis AV access, with excellent long-term patency and minimal complications due to infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…The advantages of aneurysmorrhaphy compared with ligation are the preservation of vascular access and an excellent long-term patency with minimal periprocedural complications. 10 In previously published studies, AVF closure has been shown to decrease left ventricular diameter and mass. 7,15,16 However, results of the present study show that the effect of AVF reduction on heart remodeling is not present in all patients and is dependent on cardiac index before operation but does not depend on increased AVF flow.…”
Section: Discussionmentioning
confidence: 97%
“…The advantages of aneurysmorrhaphy compared with ligation are the preservation of vascular access and an excellent long-term patency with minimal periprocedural complications. 10 In previously published studies, AVF closure has been shown to decrease left ventricular diameter and mass. 7,15,16 However, results of the present study show that the effect of AVF reduction on heart remodeling is not present in all patients and is dependent on cardiac index before operation but does not depend on increased AVF flow.…”
Section: Discussionmentioning
confidence: 97%
“…This novel approach is feasible to treat multiple extensive AVFAs but since cannulation of the repaired fi stulae has to be delayed for 4-6 weeks of recovery a temporary tunnelled dialysis catheter is needed. The 1-year primary patency results of remodelling techniques with and without support appear similar (86% [42] vs. 80-93% [19,43]). Primary patency rates of 88%, 84%, and 69% at 1, 2 and 3 years, respectively have also been reported using stapled aneurysmorrhaphy [18].…”
Section: Remodelling Techniquesmentioning
confidence: 87%
“…While several studies have reported on the treatment of high fl ow vascular access, only a few of them assess high fl ow vascular access in the presence of an aneurysm. Aneurysmorrhaphy with external mesh can signifi cantly reduce fl ow rates [35,43] and precipitate reverse cardiac remodelling with fl ow rates ≥ 1.5 L/min in patients with elevated cardiac index (≥ 3.9 L/min/m 2 ) [35]. However, aneurysmorrhaphy has proven unsuccessful with fl ow rates >2.5 L/min [19].…”
Section: Surgical Techniques For High Fl Ow Avfamentioning
confidence: 99%
“…19 ) With conventional methods, the dilated anastomosis is retained, and the mean blood pressure is higher than before surgery at the anastomosis site, which may cause the recurrence of high flow or aneurysm formation at the anastomosis site. 20 ) Moreover, even though various methods have been introduced for improving banding, 18 , 21 – 24 ) the period during which the access functions effectively after surgery is not very long that recurrence within 1 year after surgery was more than half. 13 , 16 )…”
Section: Discussionmentioning
confidence: 99%